GAMBARAN PELAKSANAAN TAMAN POSYANDU SEBAGAI BENTUK KEGIATAN PEMBERDAYAAN MASYARAKAT DI PUSKESMAS SIDOTOPO WETAN - Villia Samantha Rukmi (TEKNOLOGI MEDIS DAN JURNAL KESEHATAN UMUM, 2019)
Taman Posyandu is a service program that integrated with Pendidikan Anak Usia Dini (PAUD) and Bina Keluarga Balita (BKB). The establishment of an Integrated Service Post is intended to enable toddlers to get comprehensive services such as health information, nutritional information, parenting and obtaining protection for children. The purpose of this study was to identify a general description of the implementation of Taman Posyandu at Sidotopo Wetan Community Health Center area for community empowerment activities. The design of this study used descriptive and observational, and this research was conducted with secondary data collection, observation, and participation. Based on the data analysis, the results of the study showed that Taman Posyandu Bunda Kartini obtained the optimal value as the assessment criteria. But for Bina Keluarga Balita (BKB) services, it cannot be done optimally because the implementation cannot be done every month. Taman Posyandu Bunda Kartini is included in the UKBM because in its implementation it has included the concept of empowerment such as independence, participation, networking, and equity.